Computer-generated kinoforms of real-existing full-color 3D objects using pure-phase look-up-table method - Zheng, Huadong (2013)
A computational method based on pure-phase look-up-table (LUT) is proposed for generating kinoforms of full-color real-existing three-dimensional (3D) objects. The principle of the pure-phase LUT method is described. 3D depth as well as color information of a full-color 3D object is obtained by the full-color 3D profile measurement approach based on binocular vision. The obtained full-color 3D data is decomposed into red (R), green (G), and blue (B) channels, and kinoforms of each channel are calculated from the depth map and color information of the corresponding channel using the pure-phase LUT method. In order to reduce the speckle noise of reconstructed full-color 3D image, sequential kinoforms of each color channel are generated by adding dynamic-pseudorandom phase factor into the object domain. Numerical reconstruction and optical reconstruction with a phase-only spatial light modulator (SLM) show that, with the proposed method, full-color holographic 3D display of real-existing full-color 3D objects is available.